THE STRATEGIC ROLE OF CORPORATE FINANCE IN SUSTAINABLE BUSINESS PRACTICES. A CONCEPTUAL FRAMEWORK - SPULBAR LUCIAN FLORIN; MITRACHE LAVINIA ADELINA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2023)
This article explores the pivotal role of corporate finance in shaping and implementing sustainable business practices within the contemporary corporate landscape. In the context of an increasingly globalized and environmentally conscious world, businesses are confronted with the imperative to integrate sustainability principles into their core strategies. The field of corporate finance, traditionally associated with capital allocation and financial management, is being redefined as a strategic enabler of sustainability. This paper presents a comprehensive conceptual framework that elucidates the synergistic relationship between corporate finance and sustainable business practices. The framework posits that corporate finance plays a multifaceted role in sustainability, comprising three key dimensions. First, it encompasses the mobilization and allocation of capital towards sustainable initiatives, emphasizing the importance of impact investment and responsible financing. Second, corporate finance facilitates risk management through the incorporation of Environmental, Social, and Governance (ESG) factors, fostering long-term resilience and value creation. Lastly, it supports strategic decision-making by promoting sustainability metrics as vital performance indicators. Furthermore, this article dissects the various mechanisms through which corporate finance influences corporate sustainability, encompassing financial innovation, stakeholder engagement, and corporate governance. By recognizing that corporate finance is not merely an ancillary function but a strategic driver of sustainability, firms can harness its potential to create competitive advantages, enhance brand reputation, and secure access to sustainable financing sources